Application of iTRAQ Reagents to Relatively Quantify the Reversible Redox State of Cysteine Residues. (15th July 2012) - McDonagh, Brian; Martínez-Acedo, Pablo; Vázquez, Jesús; Padilla, C. Alicia; Sheehan, David; Bárcena, José Antonio
Abstract : Cysteines are one of the most rarely used amino acids, but when conserved in proteins they often play critical roles in structure, function, or regulation. Reversible cysteine modifications allow for potential redox regulation of proteins. Traditional measurement of the relative absolute quantity of a protein between two samples is not always necessarily proportional to the activity of the protein. We propose application of iTRAQ reagents in combination with a previous thiol selection method to relatively quantify the redox state of cysteines both within and between samples in a single analysis. Our method allows for the identification of the proteins, identification of redox-sensitive cysteines within proteins, and quantification of the redox status of individual cysteine-containing peptides. As a proof of principle, we applied this technique to yeast alcohol dehydrogenase-1 exposed in vitro to H2 O2 and also in vivo to the complex proteome of the Gram-negative bacterium Bacillus subtilis .